Synthesis, Characterization and Evaluation of Antibacterial Activity of Several New 3,4-Dimethyl Maleimides and 1,8-Naphthalimides Containing 1,3,4-Oxadiazole Ring - Al-Azzawi, Ahlam Marouf (Al-Nahrain Journal of Science, 2018)
A series of new cyclic imides (3,4-dimethyl maleimides) and (1,8-naphthalimides) substituted with 1,3,4-oxadiazole ring were prepared by following four different methods. The first one involved direct reaction of 5- substituted–2 -amino-1,3,4- oxadiazole with 3,4-dimethyl maleic anhydride under certain conditions while the second method involved reaction of 5-subsitiuted-2-amino-1,3,4-oxadiazole with 1,8- naphthalic anhydride in the presence of glacial acetic acid. The strategy used in performing the third method based on Gabrial synthesis involving treatment of 5-substituted-2-amino-1,3,4-oxadiazoles with chloro acetyl chloride to afford 2-(2-chloro acetyl amino)-1,3,4-oxadiazoles which in turn were used subsequently in reaction with 1,8-naphthalimide producing three new N-(2-acetyl amino-5-substituted-1,3,4- oxadiazole-2-yl )-1,8-naphthalimides. The strategy used in performing the fourth method based on Williamson reaction including reaction of the prepared 2-(2-chloro acetyl amino)-1,3,4- oxadiazoles with N-( hydroxy phenyl )- 3,4- dimethyl maleimides to afford nine new N-[2-oxyacetamido-5-substituted 1,3,4-oxadiazole-2- yl )phenyl]-3,4-dimethyl maleimides. Finally antibacterial activity of all the prepared new cyclic imides were evaluated against two types of bacteria and the results showed that most of the new imides posses high biological activity against these organisms.